Technology in Agriculture - Fiaz Ahmad; Muhammad Sultan (IntechOpen, 2021)
Food security is one of the primary themes of the United Nations'Sustainable Development Goals. In this regard, agricultural engineering is considered the backbone of agriculture, and agricultural mechanization is considered a helpful way to enhance crop yield and farmers'profitability. Technology in Agriculture presents research in the field of agricultural engineering technologies and applications in agricultural equipment engineering, biosystem engineering, energy systems engineering, and computers in agriculture. It provides an overview of recent advancements in agricultural engineering and examines key aspects of emerging technologies and their applications. In addition, the book explores modern methodologies such as artificial intelligence and machine learning for agricultural mechanization.